Application of comprehensive two-dimensional gas chromatography for the characterisation of the volatile composition of Honeybush tea - Ntlhokwe, Gaalebalwe Elizabeth (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016